The use of SAS for enterprise data management - Aliyu, Mansur; Mahmud, Murni (IIUM Press, 2011)
This chapter presents analysis of current data management challenges, tools, and practices in selected financial institutions in developed (i.e. United kingdom) and developing (i.e. Malaysia) countries. The chapter attempts to explore how SAS tools were used to tackle those challenges and the benefits gained through implementing SAS software. Also, the chapter examined the business data management tools and practices used by the selected organizations to propose alternative technologies for improvement and best practice